Analysis of Hydropotential and Prospects for Small Hydropower Development in Ukraine - Halych Oksana; Bilkova Eva; Nowak Petr; Riabenko Oleksandr (Environmental and Climate Technologies, 2023)
The share of electricity generation by small hydropower plants is the least among other renewable energy sources in Ukraine, although the SHPPs were widely operated in the past. The aim of the article is to analyse the hydropotential of Ukrainian rivers and review the past and present states of small hydropower engineering in Ukraine. Moreover, the article emphasizes the main directions and gives recommendations for hydropower development in Ukraine considering ecological, economic, energy and legal issues.